Nigeria’s Contribution to Africa’s Regional Integration: Assessment of its recent Performance - Garba, Dimas (African Journal of Politics and Administrative Studies, 2023)
This paper investigates the recent performance of Nigeria towards Africa’s regional integration as a major power in Africa. The main objective of the research is to determine the extent of Nigeria’s commitment to the realization of the African Union’s vision of becoming a fully integrated, prosperous and peaceful Africa; and a dynamic force at the global level. Since her independence in 1960, Nigeria has been widely acknowledged as a leading power in Africa (The Giant of Africa) by several studies because of its preponderant political, economic and militarily power; influence; and benevolent contributions regarding to the liberation and progress of Africa. However, there are hardly substantive assessments of its recent performance towards Africa’s integration. The study adopts the Hegemonic Stability Theory; and descriptive analysis method to analyze data obtained from secondary sources. Analysis of the 2016 and 2019 Regional Integration Index (ARII) reports covering the period from 2010-2019 reveals that Nigeria has performed poorly towards the continent’s integration among its peers, both at the continental and sub-regional levels. The paper concludes that Nigeria’s poor performance would significantly slow the acceleration of Africa’s integration; and the country risks losing its leadership position in Africa to its rivals, especially South Africa. It recommends that the Nigerian government should take deliberate steps in formulating and implementing policies that would improve its performance across the five dimensions of the regional integration; and it should strengthen its commitment to consolidate its leadership position in Africa, and motivate smaller countries to contribute their best.

The Challenges of Regional Integration and Effective Implementation of African Continental Free Trade Area (AfCFTA) Policy in Africa - Garba, Dimas; Wancelous, Avong (African Journal of Politics and Administrative Studies, 2023)
The paper is an investigation of the challenges of regional integration in Africa and their effects on the implementation of the African Continental Free Trade Area (AfCFTA) policy. The major objective of the paper is to proffer solutions to the challenges for the effective actualization of the policy. The assumptions of the neo-liberal theory were used to support the AfCFTA initiative to promote economic growth and development in Africa. The data used to advance the argument were obtained from secondary sources of data collection. The study finds that language barrier, multiple currencies, porosity of borders, foreign interference, political instability and insecurity, poor human development, over-lapping of membership of sub-regional organizations, poor state of infrastructure, and state-centric nature of integration initiatives are some of the core challenges hindering the effective execution of the AfCFTA policy. The study recommends that the African Union (AU) should intensify effort at realizing a single currency policy for Africa; design comprehensive regional security architecture to include high technological surveillance, joint air and ground border patrol among member states of Regional Economic Communities (RECs) to address trans-border crimes and insecurity. There should also be institutionalization of counterpart funding among AU member-states for infrastructural development; and encouragement of private and civil society participation in the integration initiative, among others. In concludes that if the challenges identified are not effectively addressed, it will be very difficult for the AU to successfully realize the objectives of the AfCFTA policy.
Keywords: AfCFTA Policy; Africa; Challenges; Implementation; Regional integration